2015
DOI: 10.1016/j.solener.2015.07.024
|View full text |Cite
|
Sign up to set email alerts
|

An empirical approach to parameterizing photovoltaic plants for power forecasting and simulation

Abstract: The aim of this work is to develop an algorithm that can utilize historical PV power measurements to establish the parameters of a physical model for power production. The chosen approach consists in evaluating the parameters of a PV model that maximize the likelihood that simulations match with power measurements. The proposed method offers advantages beyond the standard approaches used for the simulation or prediction of PV power production, as it makes maxinnun use of the information typically available on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 7 publications
1
20
0
Order By: Relevance
“…The physical method is based on the geographical information of the photovoltaic power station, detailed meteorological data, and the operation equation of the PV module [13]. Saint-Drenan et al [14] developed a physical method that can employ historical PV power data to found the parameters equation of a physical model for power output. On the one hand, the modeling process is relatively complex.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The physical method is based on the geographical information of the photovoltaic power station, detailed meteorological data, and the operation equation of the PV module [13]. Saint-Drenan et al [14] developed a physical method that can employ historical PV power data to found the parameters equation of a physical model for power output. On the one hand, the modeling process is relatively complex.…”
Section: Introductionmentioning
confidence: 99%
“…calculate the error of base learner by Formula (set, output the final hypotheses by Formula (14)(14) …”
mentioning
confidence: 99%
“…Though more practical than the classical approaches, these statistical approaches are also time consuming because of the handling of the data and they cannot be applied in regions where no training data is available. Another common practice consists in estimating the total power generated in a region by upscaling the power generated by a subset of reference plants (Schierenbeck et al, 2010;Lorenz and Heinemann, 2012;Shaker et al, 2015Shaker et al, , 2016Saint-Drenan et al, 2016;Bright et al, 2017;Pierro et al, 2017;Killinger et al, 2017). The major obstacles to this practice is on the one hand the establishment of criteria on the selection of the plants that are statistically representative of the region and their number, and on the other hand, the access to measurements of the selected plants.…”
Section: Introductionmentioning
confidence: 99%
“…• Researchers commonly face the task of analyzing the performance of a large number of PV sites (Killinger et al, 2017a(Killinger et al, , 2017bSaint-Drenan et al, 2015) to gain insight into the performance of the systems in real life conditions. This requires irradiance data for the investigated period which can come from either satellite measurements, or nearby meteorological stations.…”
Section: Introductionmentioning
confidence: 99%